Immunogenomic stratification of the tumor microenvironment in surgically treated non-small cell lung cancer: A Ukrainian single-center experience - Y. Moskalenko; N. Hyriavenko; T. Derevianko (Regulatory Mechanisms in Biosystems, 2025)
Non-small cell lung cancer (NSCLC) remains the leading cause of cancer-related mortality worldwide. Despite radical surgical resection, recurrence is frequent, highlighting the need for improved stratification methods and adjuvant therapeutic strategies. Immunotherapy has demonstrated efficacy in metastatic NSCLC; however, its role in surgically treated patients is still under inve s tigation. This study aimed to analyze the immune landscape of the tumor immune microenvironment in resected NSCLC spec i mens, identify immune clusters, and evaluate their relationship with patient survival and tumor molecular characteristics. A single-center retrospective study was conducted on 42 patients with stage I–IIIB NSCLC who underwent surgical resection between 2015 and 2018. All patients received platinum-based adjuvant chemotherapy; 35.7% received additional atezolizumab immunotherapy, and 11.9% received adjuvant radiotherapy. Tumor samples were assessed via immunohistochemistry for CD8⁺ cytotoxic T cells, FoxP3⁺ regulatory T cells, CD68⁺ (M1), and CD163⁺ (M2) macrophages in both tumor islets and stroma. Expression levels were stratified into high/low groups based on validated cut-offs. PD-L1 status was also evaluated. Seven immune markers were analyzed using principal component analysis and k-means clustering (k = 2) to define immune phenotypes. Next-generation sequencing was performed using the AmoyDx Essential Panel targeting ten major driver mutations. Survival was assessed using Kaplan-Meier estimates and log-rank tests. Two distinct immune phenotypes were identified: an immunoactive cluster (n = 14) with high CD8⁺ and M1 infiltration, and an immunosuppressive cluster (n = 28) characterized by increased FoxP3⁺ and M2 expression. Although not statistically significant, the immunoactive group showed a trend toward improved outcomes: median progression-free survival was 98.8 in the immunoactive cluster vs. 27.8 months ( P = 0.543) in the immunosuppressive cluster , and overall survival was 114.5 in the immunoactive cluster vs. 38.1 months ( P = 0.435) in the immunosuppressive cluster . NGS revealed mutations in 26.2% of tumor samples (KRAS 16.7%, EGFR 4.8%, ALK 2.4%, BRAF 2.4%), with no significant difference between clusters ( P = 0.8 10 ), suggesting independence between molecular and immune profiles. In conclusion, immune-based stratification identified distinct TME phenotypes associated with survival trends in surgically treated NSCLC. Integrating immunohistochemistry and next-generation sequencing may improve personalized adjuvant treatment selection. Larger studies are needed to validate these findings.